Construction of a High-Density Genetic Map and Identification of Quantitative Trait Loci for Nitrite Tolerance in the Pacific White Shrimp (Litopenaeus vannamei) - Peng, Min; Zeng, Digang; Zhu, Weilin; Chen, Xiuli; Yang, Chunling; Liu, Qingyun; Li, Qiangyong; Wang, Huanling; Liu, Hong; Liang, Jingzhen; Lin, Yong; Chen, Xiaohan; et al. (Frontiers in Genetics, 2020)
Nitrite is a major environmental toxin in aquaculture systems that disrupts multiple physiological functions in aquatic animals. Although nitrite tolerance in shrimp is closely related to successful industrial production, few genetic studies of this trait are available. In this study, we constructed a high-density genetic map of Litopenaeus vannamei with 17,242 single nucleotide polymorphism markers spanning 6,828.06  centimorgans (cM), with an average distance of 0.4 cM between adjacent markers on 44 linkage groups (LGs). Using this genetic map, we identified two markers associated with nitrite tolerance. We then sequenced the transcriptomes of the most nitrite-tolerant and nitrite-sensitive individuals from each of four genetically distinct L. vannamei families (LV-I–4). We found 2,002, 1,983, 1,954, and 1,867 differentially expressed genes in families LV-1, LV-2, LV-3, and LV-4, respectively. By integrating QTL and transcriptomics analyses, we identified a candidate gene associated with nitrite tolerance. This gene was annotated as solute carrier family 26 member 6 (SLC26A6). RNA interference (RNAi) analysis demonstrated that SLC26A6 was critical for nitrite tolerance in L. vannamei. The present study increases our understanding of the molecular mechanisms underlying nitrite tolerance in shrimp and provides a basis for molecular-marker-assisted shrimp breeding.